PCS-15 Study Anatomy of Testis and Epididymis of Timorese Fruit Bats (Pteropus vampyrus) - Yulfia N Selan; Filphin A Amalo; Inggrid T Maha; Antin Y N Widi; Agnes L Tanjung (Hemera Zoa, 2018)
Fruit bats (Pteropus vampyrus) is one of the bats in Timor Island, East Nusa Tenggara (NTT). Fruit bats have unique behaviour when mating which is hanging upside down (Corbet and Hill, 1992). The ability of male bat in maintaining the position when mating is according to the characteristics of male fruit bat reproduction system morphology. Testes are male genital organs which synthesis androgen hormone (especially testosterone) and the site where spermatogenesis takes place and eventually producing sperm. Epididymis plays role in transporting, storaging and maturating the sperm (Syahrum et al., 1994).